ASEAN STATES IN CHINESE FOREIGN POLICY: ON COURSE TO SPLIT OR TO REACH “NEW CONSENSUS”? - A. D. Dikarev (Сравнительная политика, 2018)
Dynamics of political and trade relations betweenChina, ASEAN organization and its members, problems of regional geopolitics with regard to the conflict on features and resources ofSouth China Seaare analyzed. Since the second half of the 1990’s,Chinahas been consistently establishing relations of “strategic partnership” with individual ASEAN countries. The second decade of the 21st century witnessed a fundamental turnaround: all sides try to fix their economic interests in the region while political tensions increase gradually. Since 2013 following the promotion of the Belt and Road Initiative, a new round of tension began, in other words, intensive attempts to consolidate sovereignty over a resourceful and strategically important territory avoiding at the same time reduction of the volume of regional economic cooperation. In general, despite fluctuations,Chinaremains the main trade and economic partner for most ASEAN countries, therefore their ability to exercise political independence is significantly limited.